Pengaruh Profitabilitas Kebijakan Dividen Dan Kebijakan Utang Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2010-2013 - Pranindyastuti, Tika; , Drs. Syamsudin, M.M (2016)
This study aims to determine the effect of variable Profitability, Dividend Policy and Debt Policy on Corporate Value. The research sample totaled 10 in companies listed on the Indonesian Stock Exchange (BEI) by the amount of data as much as 40 to the period 2010-2013. The sampling technique using purposive sampling techniques or retrieval of data in accordance with the criteria used in this study. The method of analysis used in this study with descriptive analysis, multiple linear regression analysis, the classical assumption test including normality test, multicollinearity test, autocorrelation test, and test heterokesdatisitas. In addition there is also a hypothesis test using t test, F test at the significant level of 0.05 and a coefficient of determination. ROE profitability proxy variables have positive and significant impact on the value of the company proxy PBV. Dividend policy variables that proxy DPR no significant effect on the value of the company PBV). Policy variables that proxy DER debt has a significant negative effect on firm value (PBV) The results of testing the F-test analysis has been done, the variable profitability (Retrun on Equity), dividend policy (Dividend Payout Ratio), and debt policy (Debt to Equity Ratio) jointly affect the value of the company (Price to Book Value) obtained that Fhitung 17.523 with a significance value (0.000), this indicates that the calculated value is much less significant than the standards that have significant value ditentukan. Hasil of the coefficient of determination, Rsquare obtained 0.594 means that 59.4% variable price to book value can be explained by the ROE, DPR, and DER remaining 40.6% is explained by factors beyond the researchmodel.